The effect of nutrition counseling on growth development and success in star wrestlers: Nutrition counseling and star wrestlers - Sökülmez Kaya, Pınar; Ulus, Canan Asal (Progress in Nutrition, 2021)
ABSTRACT: The aim of this study is to investigate the feeding habits of national wrestlers. 36 volunteer male newcomer national wrestlers who were between 13-15 years old participated in the study. One group of the wrestlers in two different regions of the same age was given nutrition education and nutrition counseling by the researcher for one year. The obtained data were saved to the computer using SPSS 13.5 package program. In all tests, p <0.05 was considered significant. Group I had more length growth than the other group. The hip circumference and upper middle arm circumference were found to be larger in Group I than in Group II (p<0.05). There was a statistically significant difference between the degree of wrestlers in the competitions (p<0.05). About one in twenty athletes in Group I who received continuous nutritional counseling consumed carbohydrate, vitamin B1, vitamin B12 and calcium below RDA’s recommended values for adolescent children. Among group II athletes food items consumed below recommendation and percentages were; 5.9% for total energy, 41.2% for carbohydrate, 70.6% for fiber, 47.1% for vitamin A, 17.6% for vitamin E, 94.1% for vitamin B1, 47.1% for vitamin B2, 58.8% for vitamin B6, 88.2% for biotin, 70.6% for folic acid, 94.1% vitamin for C, 58.8% for potassium, 100.0% for calcium, 29.4% for magnesium, 11.8% for phosphorus, 17.6% for iron, 76.5% for pantothenic acid. The athletes of the wrestling, have improved their performance and growth positively when they have adequate and balanced nutrition counseling.